The South China Sea Dispute: An Overview - K Pattnaik, Prabir; Das, Sidhartha (International Journal of Psychosocial Rehabilitation, 2025)
This research paper talks about the South China Sea dispute and the other countries involved in this dispute which include China in the forefront which claims its sovereignty over majority of the sea, this dispute has involvement of the countries like Brunei, Malaysia, Vietnam, Indonesia and Philippines also. The paper also discusses the key issues involved in the dispute before it discusses the legal perspectives and environmental impacts pertaining to the issues. The paper concludes with discussing about the powerlessness of conventions such as UNCLOS in front of the world powers like China.